2007
DOI: 10.1029/2006gl027557
|View full text |Cite
|
Sign up to set email alerts
|

Estimates of the precision of GPS radio occultations from the COSMIC/FORMOSAT‐3 mission

Abstract: [1] The Constellation Observing System for Meteorology Ionosphere and Climate (COSMIC)/Formosa Satellite 3 (FORMOSAT-3) is a six-satellite radio occultation mission that was launched in mid-April, 2006. The close proximity of the COSMIC satellites provides a unique opportunity to estimate the precision of the radio occultation remote sensing technique from closely collocated occultations (<10 km separation of tangent points). The RMS difference of refractivity between 10 and 20 km altitude is less than 0.2%, w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

11
328
0
1

Year Published

2008
2008
2015
2015

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 366 publications
(340 citation statements)
references
References 23 publications
11
328
0
1
Order By: Relevance
“…It was concluded that the accuracy of NmF2 yields around 20% of its absolute level, which was later confirmed by Tsai et al (2001). Furthermore, to estimate the absolute precision of the classical Abel inversion, Schreiner et al (2007) studied the accuracy of N e by co-located F-3/C EDPs and obtained a root-mean-square (RMS) difference of approximately 10 9 el/m 3 , a value which indicates already, that rough discrepancies cannot be ruled out by using the classical approach.…”
Section: Introductionmentioning
confidence: 81%
“…It was concluded that the accuracy of NmF2 yields around 20% of its absolute level, which was later confirmed by Tsai et al (2001). Furthermore, to estimate the absolute precision of the classical Abel inversion, Schreiner et al (2007) studied the accuracy of N e by co-located F-3/C EDPs and obtained a root-mean-square (RMS) difference of approximately 10 9 el/m 3 , a value which indicates already, that rough discrepancies cannot be ruled out by using the classical approach.…”
Section: Introductionmentioning
confidence: 81%
“…Rocken et al, 2000;Schreiner et al, 2009). The comparison of CHAMP electron density profiles with electron density profiles deduced from the radio occultation measurements onboard the Formosat-3/COSMIC satellites, which are provided by the data center TACC/CDAAC, revealed good agreement with a RMS of less than 1.4×10 11 m −3 for NmF2, cf.…”
Section: Introductionmentioning
confidence: 99%
“…A summary of the mission objectives and early results with COSMIC/FORMOSAT-3 (referred to as COSMIC hereafter) is given by Anthes et al (2008). In addition, Schreiner et al (2007) have shown that refractivity profiles derived from the COS-MIC measurements have a precision of ∼0.2% of the observed value, between heights of 10 and 20 km.…”
Section: Introductionmentioning
confidence: 99%